Sistem Informasi Jadwal Pengiriman Gas LPG Berbasis Push Notification Android - Liza Safitri; Amin Amin (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2022)
LPG distribution is carried out on a scheduled basis by PT. Adri Jaya Sakti Tanjungpinang to retailers. The delivery of information from agents to retailers is done by direct voice calls, this is less effective because Customer Service delivers the same things over and over again. In addition, there is a lot of information that is not conveyed because the retailer number can change from time to time.Push notification-based information delivery methods can send real-time information to recipients by using the Application ID installed on the smartphone. The push notification method used uses the OneSignal API help. From the design stage to the implementation stage, it can be denied that the Android-based push notification information system can send real-time gas delivery scheduling information to clients registered in the database.